当前位置:网站首页>[combinatorics] summary of combinatorial identities (eleven combinatorial identities | proof methods of combinatorial identities | summation methods)*
[combinatorics] summary of combinatorial identities (eleven combinatorial identities | proof methods of combinatorial identities | summation methods)*
2022-07-03 16:08:00 【Programmer community】
List of articles
- One 、 Eleven combinatorial identities
- Two 、 Combinatorial identity Method of proof
- 3、 ... and 、 Combinatorial number Sum up
∑
\sum
∑ Method
Combinatorial identity reference blog :
- 【 Combinatorial mathematics 】 Binomial theorem and combinatorial identities ( binomial theorem | Three combinatorial identities recursion | recursion 1 | recursion 2 | recursion 3 Pascal / Yang Hui's trigonometric formula | Combination analysis method | Characteristics of recursive combinatorial identities )
- 【 Combinatorial mathematics 】 Combinatorial identity ( Recurrence Combinatorial identity | Change the next term to sum Combinatorial identity Simple and | Change the next term to sum Combinatorial identity Staggered and )
- 【 Combinatorial mathematics 】 Combinatorial identity ( Change the next term to sum 3 Combinatorial identity | Change the next term to sum 4 Combinatorial identity | binomial theorem + Derivation Prove the combinatorial identity | Use known combinatorial identities to prove combinatorial identities )
- 【 Combinatorial mathematics 】 Combinatorial identity ( Review of eight combinatorial identities | Combinatorial identity product 1 | prove | Use scenarios )
- 【 Combinatorial mathematics 】 Combinatorial identity ( Combinatorial identity Sum of product 1 | Sum of product 1 prove | Combinatorial identity Sum of product 2 | Sum of product 2 prove )
One 、 Eleven combinatorial identities
1 . Combinatorial identity ( recursion ) :
( 1 ) recursion 1 :
(
n
k
)
=
(
n
n
−
k
)
\dbinom{n}{k} = \dbinom{n}{n-k}
(kn)=(n−kn)①
( 2 ) recursion 2 :
(
n
k
)
=
n
k
(
n
−
1
k
−
1
)
\dbinom{n}{k} = \dfrac{n}{k} \dbinom{n - 1}{k - 1}
(kn)=kn(k−1n−1)②
( 3 ) recursion 3 ( Pascal / Yang Hui's trigonometric formula ) :
(
n
k
)
=
(
n
−
1
k
)
+
(
n
−
1
k
−
1
)
\dbinom{n}{k} = \dbinom{n - 1}{k} + \dbinom{n - 1}{k - 1}
(kn)=(kn−1)+(k−1n−1)③
2 . Review the combinatorial identities of summation under four variables : The combinatorial identity introduced earlier The number of combinations in
(
n
k
)
\dbinom{n}{k}
(kn) , Is the next item
k
k
k Have been accumulating changes , have
∑
k
=
0
n
\sum\limits_{k=0}^{n}
k=0∑n Cumulative property , Previous item
n
n
n It is the same. ;
( 1 ) Simple and :
∑
k
=
0
n
(
n
k
)
=
2
n
\sum\limits_{k=0}^{n}\dbinom{n}{k} = 2^n
k=0∑n(kn)=2n④
( 2 ) Staggered and :
∑
k
=
0
n
(
−
1
)
k
(
n
k
)
=
0
\sum\limits_{k=0}^{n} (-1)^k \dbinom{n}{k} = 0
k=0∑n(−1)k(kn)=0⑤
( 3 ) Change the next term to sum 3 :
∑
k
=
0
n
k
(
n
k
)
=
n
2
n
−
1
\sum\limits_{k=0}^{n} k \dbinom{n}{k} = n 2^{n-1}
k=0∑nk(kn)=n2n−1⑥
( 4 ) Change the next term to sum 4 :
∑
k
=
0
n
k
2
(
n
k
)
=
n
(
n
+
1
)
2
n
−
2
\sum_{k=0}^{n} k^2 \dbinom{n}{k} = n ( n+1 ) 2^{n-2}
∑k=0nk2(kn)=n(n+1)2n−2⑦
3 . Change the upper term to sum :
∑
l
=
0
n
(
l
k
)
=
(
n
+
1
k
+
1
)
\sum\limits_{l=0}^{n} \dbinom{l}{k} = \dbinom{n + 1}{k + 1}
l=0∑n(kl)=(k+1n+1)⑧
4 . product :
∑
l
=
0
n
(
l
k
)
=
(
n
+
1
k
+
1
)
\sum\limits_{l=0}^{n} \dbinom{l}{k} = \dbinom{n + 1}{k + 1}
l=0∑n(kl)=(k+1n+1)⑨
5 . Sum of product :
( 1 ) Combinatorial identity ( Sum of product ) 1 :
∑
k
=
0
r
(
m
k
)
(
n
r
−
k
)
=
(
m
+
n
r
)
,
r
=
min
{
m
,
n
}
\sum\limits_{k=0}^{r}\dbinom{m}{k}\dbinom{n}{r-k} = \dbinom{m + n }{r} , \ \ \ \ \ \ r= \min \{ m, n \}
k=0∑r(km)(r−kn)=(rm+n), r=min{ m,n}⑩
( 2 ) Combinatorial identity ( Sum of product ) 2 :
∑
k
=
0
r
(
m
k
)
(
n
k
)
=
(
m
+
n
m
)
\sum\limits_{k=0}^{r}\dbinom{m}{k}\dbinom{n}{k} = \dbinom{m + n }{m}
k=0∑r(km)(kn)=(mm+n)⑪
Two 、 Combinatorial identity Method of proof
1 . Known combinatorial identities are substituted into : Known
11
11
11 A combinatorial identity is substituted into
2 . binomial theorem
n
n
n It's a positive integer. , For everything
x
x
x and
y
y
y , There are the following theorems :
(
x
+
y
)
n
=
∑
k
=
0
n
(
n
k
)
x
k
y
n
−
k
(x + y)^n = \sum_{k=0}^n \dbinom{n}{k}x^k y^{n-k}
(x+y)n=k=0∑n(kn)xkyn−k
(
n
k
)
\dbinom{n}{k}
(kn) Express
n
n
n Yuan centralized retrieval
k
k
k Number of combinations of elements , yes Number of sets
C
(
n
,
k
)
C(n,k)
C(n,k) Another way of writing ;
Another common form (
y
=
1
y = 1
y=1 ) :
(
1
+
x
)
n
=
∑
k
=
0
n
(
n
k
)
x
k
(1 + x)^n = \sum_{k=0}^n \dbinom{n}{k}x^k
(1+x)n=k=0∑n(kn)xk
Basic summation formula (
x
=
y
=
1
x = y =1
x=y=1 ) :
2
n
=
∑
k
=
0
n
(
n
k
)
2^n = \sum_{k=0}^n \dbinom{n}{k}
2n=k=0∑n(kn)
3 . Derivation of power series 、 integral
Derivation of power function : ( Very important )
- Primitive function :
y
=
x
n
y = x^n
y=xn
- Corresponding derivative :
y
′
=
n
x
n
−
1
y' = nx^{n-1}
y′=nxn−1
The derivative of a constant is
0
0
0 ;
Four operations of derivative :
(
u
±
v
)
′
=
u
′
±
v
′
(u \pm v)' = u' \pm v'
(u±v)′=u′±v′
Reference resources :
- derivative - Baidu Encyclopedia
- Combinatorial identity ( Change the next term to sum ) Sum of variable coefficients 1 prove ( binomial theorem + Derivation )
4 . Induction
Mathematical induction describe A proposition related to natural numbers
P
(
n
)
P(n)
P(n) ,
According to different questions , Set up
n
n
n The minimum value , Usually from
0
0
0 Start ,
( 1 ) The proof is divided into the following two steps :
① Inductive basis : First prove that Inductive basis , If it is proved that
P
(
0
)
P(0)
P(0) It's true ;
② Induction steps : according to Types of mathematical induction , Prove in different ways , Here you are First, mathematical induction and Second, mathematical induction Two kinds of induction ;
( 1 ) Mathematical induction :
① First, mathematical induction : from
P
(
n
)
P(n)
P(n) deduction
P
(
n
+
1
)
P(n + 1)
P(n+1)
P
(
0
)
P(0)
P(0) It's true
hypothesis
P
(
n
)
P(n)
P(n) It's true , prove
P
(
n
+
1
)
P(n + 1)
P(n+1) It's true
② Second, mathematical induction : All less than
n
n
n Of
P
(
0
)
,
P
(
1
)
,
⋯
,
P
(
n
−
1
)
P(0) , P(1), \cdots , P(n-1)
P(0),P(1),⋯,P(n−1) It's all true , deduction
P
(
n
)
P(n)
P(n) It's true ;
P
(
0
)
P(0)
P(0) It's true
Assume that all are less than
n
n
n The natural number of
k
k
k , proposition
P
(
k
)
P(k)
P(k) It's all true , namely
P
(
0
)
,
P
(
1
)
,
⋯
,
P
(
n
−
1
)
P(0) , P(1), \cdots , P(n-1)
P(0),P(1),⋯,P(n−1) It's all true , deduction
P
(
n
)
P(n)
P(n) It's true ;
Symbolized as :
P
(
0
)
∧
P
(
1
)
∧
⋯
∧
P
(
n
−
1
)
→
P
(
n
)
P(0) \land P(1) \land \cdots \land P(n-1) \to P(n)
P(0)∧P(1)∧⋯∧P(n−1)→P(n)
Reference resources : 【 Combinatorial mathematics 】 Introduction to combinatorics ( Combination thought 2 : Mathematical induction | Generalization of mathematical induction | Multiple inductive thoughts )
5 . Combinatorial analysis
When using the combination analysis method to prove the combination number , Specify the set first , Specify elements , Specify two counting problems , On both sides of the formula are the counts of the same problem ;
( 1 ) Specify the collection : Specify the set in which the count is generated ;
( 2 ) Specify the counting problem : The following two counting problems are the counting of the same problem ;
- ① problem 1 : The left side of the equal sign represents the counting problem ;
- ② problem 2 : The right side of the equal sign represents the counting problem ;
( 3 ) Equivalent description : It shows that the two counting problems are the same ;
Reference resources :
- 【 Combinatorial mathematics 】 Combinatorial identity ( Combinatorial identity Sum of product 1 | Sum of product 1 prove | Combinatorial identity Sum of product 2 | Sum of product 2 prove ) Two 、 Combinatorial identity ( Sum of product ) 1 prove
The above proof method , According to specific certification requirements , Choose the appropriate proof method ;
3、 ... and 、 Combinatorial number Sum up ∑
\sum
∑ Method
For formulas containing combinatorial numbers Sum up
∑
\sum
∑ Method
1 . Use Pascal formula :
recursion 3 ( Pascal / Yang Hui's trigonometric formula ) :
(
n
k
)
=
(
n
−
1
k
)
+
(
n
−
1
k
−
1
)
\dbinom{n}{k} = \dbinom{n - 1}{k} + \dbinom{n - 1}{k - 1}
(kn)=(kn−1)+(k−1n−1)③
( 1 ) Merge item :
(
n
k
)
\dbinom{n}{k}
(kn) Can be reduced to
(
n
−
1
k
)
+
(
n
−
1
k
−
1
)
\dbinom{n - 1}{k} + \dbinom{n - 1}{k - 1}
(kn−1)+(k−1n−1) The sum of the ;
( 2 ) This recursion , Used to split items :
Can be
(
n
k
)
\dbinom{n}{k}
(kn) Split into
(
n
−
1
k
)
+
(
n
−
1
k
−
1
)
\dbinom{n - 1}{k} + \dbinom{n - 1}{k - 1}
(kn−1)+(k−1n−1) The sum of the ; In actual use , Often encounter some items listed , Yes
(
n
−
1
k
)
+
(
n
−
1
k
−
1
)
\dbinom{n - 1}{k} + \dbinom{n - 1}{k - 1}
(kn−1)+(k−1n−1) The number of combinations of forms , Can be merged into one
(
n
k
)
\dbinom{n}{k}
(kn) ;
( 3 ) It can also be used by deformation , Put one of them , Become the difference between two of them ;
take
(
n
−
1
k
)
\dbinom{n - 1}{k}
(kn−1) Split into
(
n
k
)
−
(
n
−
1
k
−
1
)
\dbinom{n}{k} -\dbinom{n - 1}{k - 1}
(kn)−(k−1n−1) The difference between the ;
take take
(
n
−
1
k
−
1
)
\dbinom{n - 1}{k - 1}
(k−1n−1) Split into
(
n
k
)
−
(
n
−
1
k
)
\dbinom{n}{k} -\dbinom{n - 1}{k}
(kn)−(kn−1) The difference between the ;
In a stack of summation combinatorial numbers , Split into the difference between two numbers , Can offset many combinations ;
It is often used for simplification in large sum formulas ;
2 . Sum of series :
3 . Observations and results , Prove by mathematical induction :
Guess the result of a sum , Then use induction to prove ;
4 . Use the known formula to sum :
边栏推荐
- "Remake Apple product UI with Android" (2) -- silky Appstore card transition animation
- [combinatorics] combinatorial identities (sum of variable terms 3 combinatorial identities | sum of variable terms 4 combinatorial identities | binomial theorem + derivation to prove combinatorial ide
- Jmeter线程组功能介绍
- 用同花顺炒股开户安全吗?
- [redis foundation] understand redis persistence mechanism together (rdb+aof graphic explanation)
- Redis在Windows以及Linux系统下的安装
- Microservices - load balancing ribbon
- 《微服务设计》读书笔记(下)
- 切入点表达式
- 六月 致 -.-- -..- -
猜你喜欢
请做好3年内随时失业的准备?
Wechat payment -jsapi: code implementation (payment asynchronous callback, Chinese parameter solution)
The accept attribute of the El upload upload component restricts the file type (detailed explanation of the case)
Function introduction of JMeter thread group
How to thicken the brush in the graphical interface
Getting started with Message Oriented Middleware
Slam learning notes - build a complete gazebo multi machine simulation slam from scratch (I)
TCP拥塞控制详解 | 3. 设计空间
[系统安全] 四十三.Powershell恶意代码检测系列 (5)抽象语法树自动提取万字详解
[list to map] collectors Tomap syntax sharing (case practice)
随机推荐
Function introduction of JMeter thread group
The difference between RAR and zip files
Automatic generation of client code from flask server code -- Introduction to flask native stubs Library
[combinatorics] combinatorial identity (sum of variable upper terms 1 combinatorial identity | summary of three combinatorial identity proof methods | proof of sum of variable upper terms 1 combinator
"Remake Apple product UI with Android" (2) -- silky Appstore card transition animation
2022年Q2加密市场投融资报告:GameFi成为投资关键词
Microservice - declarative interface call openfeign
Backtracking method to solve batch job scheduling problem
Calibre LVL
Slam learning notes - build a complete gazebo multi machine simulation slam from scratch (4)
Find mapping relationship
Uploads labs range (with source code analysis) (under update)
Slam learning notes - build a complete gazebo multi machine simulation slam from scratch (I)
Slam learning notes - build a complete gazebo multi machine simulation slam from scratch (III)
Three dimensional reconstruction of deep learning
一些事情的反思
Detailed explanation of string function and string function with unlimited length
[web security] - [SQL injection] - error detection injection
初试scikit-learn库
高等数学(第七版)同济大学 习题2-1 个人解答